Perbedaan dan Interaksi Pembelajaran Menggunakan Model Example dan non-example terhadap Keterampilan Membaca Permulaan pada Kelas I-A Little Camel Islamic International School Mojokerto. - Al-Mahali, Ahmad Mustofa Jalalluddin (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2020)
The purpose of this research is. (1) Describe the differences in the pre-reading skills of children who were taught before using the example and non-example model learning and after using the example and non-example model learning in Class IA Little Camel Islamic International School Mojokerto (2) describing the learning interactions using the example learning model and non-example of pre-reading skills in Class IA Little Camel Islamic International School Mojokerto. This study uses a quantitative approach with comparative and experimental types. The quasi-time series one-group Pre-test-Post-test experimental design with the research object in Class I-A Little Camel Islamic International School Mojokerto as many as 18 children consisting of 7 boys and 11 girls. Data collection using interviews and tests using WhatsApp media. The data analysis used the Two Ways Anava analysis technique, namely the ANOVA test which was based on the observation of two criteria. From the results of the analysis concluded: 1) There are differences in the pre-reading skills of children who were taught before using the example and non-example model learning and after using the example and non-example model learning in Class I-A at Little Camel Islamic International School Mojokerto; 2) There is a learning interaction using the example and non-example learning model on pre-reading skills in Class I-A Little Camel Islamic International School Mojokerto.